2019
DOI: 10.1186/s12964-019-0354-2
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid response by Halofuginone in Cancer cells triggers autophagy through proteasome degradation of mTOR

Abstract: Background In the event of amino acid starvation, the cell activates two main protective pathways: Amino Acid starvation Response (AAR), to inhibit global translation, and autophagy, to recover the essential substrates from degradation of redundant self-components. Whether and how AAR and autophagy (ATG) are cross-regulated and at which point the two regulatory pathways intersect remain unknown. Here, we provide experimental evidence that the mammalian target of rapamycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…To explore the potential functions of AC124804.1 and MIR34AHG, the co-expressed protein-coding mRNAs of these lncRNAs were investigated using a Pearson correlation coefficient test followed by GO and KEGG functional enrichment analyses. These analyses demonstrated that the potential underlying molecular mechanisms of AC124804.1 function were pathways involving proteasome, peroxisome and SNARE interactions in vesicular transport, which have confirmed roles in tumorigenesis and progression in previous studies (37)(38)(39). MIR34AHG is the host gene of miR-34a and consequently may have biological functions associated with the miR-34 family, which may have suppressive functions in LUAD as previously demonstrated (40,41).…”
Section: Discussionsupporting
confidence: 83%
“…To explore the potential functions of AC124804.1 and MIR34AHG, the co-expressed protein-coding mRNAs of these lncRNAs were investigated using a Pearson correlation coefficient test followed by GO and KEGG functional enrichment analyses. These analyses demonstrated that the potential underlying molecular mechanisms of AC124804.1 function were pathways involving proteasome, peroxisome and SNARE interactions in vesicular transport, which have confirmed roles in tumorigenesis and progression in previous studies (37)(38)(39). MIR34AHG is the host gene of miR-34a and consequently may have biological functions associated with the miR-34 family, which may have suppressive functions in LUAD as previously demonstrated (40,41).…”
Section: Discussionsupporting
confidence: 83%
“…Remarkably, despite increasing autophagosome biogenesis, UPS inhibition does not affect autophagy flux [110]. This fits with recent evidence showing that UPS activity, rather than inhibition, promotes autophagy both by fostering the nuclear translocation of TFEB, and remarkably, by degrading mTOR itself, leading to its downregulation and detachment from the lysosomes [111]. In baseline conditions the turnover of the transmembrane autophagy protein Atg9 is also carried out by the UPS, while this is impeded upon autophagy-inducing stimuli such as starvation or rapamycin treatment [112].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 89%
“…In this functional setting, the merging between UPS and autophagy is defined as "proteaphagy". This is in line with studies indicating a reciprocal regulation between the two cell-clearing systems, with UPS behaving as a sentinel in sensing and regulating autophagy, and vice versa [68,[108][109][110][111][112][113]. In detail, UPS regulates the duration and amplitude of the autophagy response by controlling the stability of Unc-51 like autophagy activating kinase (ULK1)/Atg1 complex as well as mTOR and transcription factor EB (TFEB) kinases [108][109][110].…”
Section: Emerging Mechanisms Underlying Autophagy and Proteasome Crossupporting
confidence: 86%
See 1 more Smart Citation
“…Under nutrient rich conditions, activation of mTORC1 supports cancer cells growth. In periods of cellular stress, low levels of amino acids or absent ATP induces mTORC1 inhibition, which subsequently activates a compensatory mechanism named autophagy [25]. Autophagy is a highly regulated pathway essential for cell survival in nutrient-deprived conditions, complementing the classical pathways like glycolysis.…”
Section: Cancer Metabolismmentioning
confidence: 99%